2020
DOI: 10.1038/s41598-020-75532-5
|View full text |Cite
|
Sign up to set email alerts
|

Organic nitrogen steadily increasing in Norwegian rivers draining to the Skagerrak coast

Abstract: Declining atmospheric nitrogen (N) deposition, through reduction in the direct input of inorganic N, may result in less inorganic N being leached from soils to freshwaters (dissolved inorganic N = DIN). Declining sulphur deposition, through reducing the ionic strength in soil water, increases the solubility and mobility of organic soil compounds and may result in increased leaching of organically bound N to freshwaters (total organic N = TON). It is unknown to which extent these two independents and opposing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
7
1
Order By: Relevance
“…At Heiligendamm, the bulk DOC, DON, POC, and PON concentrations did not change significantly within the examined time frame from 2010 to 2020, though several recent studies show increased carbon and nitrogen concentrations in rivers that are exported to the coastal ocean in different northern European regions (Worrall et al, 2004;Deininger et al, 2020;Lepistö et al, 2021). Unlike Deininger et al (2020), who found DON to the Skagerrak from Norwegian rivers to increase from 1990 to 2017, we detected no change in DON concentration. This may be due to the fact that our time series for DON starting in 2010 was much shorter than their dataset covering 27 years.…”
Section: Long Term Trendscontrasting
confidence: 83%
See 2 more Smart Citations
“…At Heiligendamm, the bulk DOC, DON, POC, and PON concentrations did not change significantly within the examined time frame from 2010 to 2020, though several recent studies show increased carbon and nitrogen concentrations in rivers that are exported to the coastal ocean in different northern European regions (Worrall et al, 2004;Deininger et al, 2020;Lepistö et al, 2021). Unlike Deininger et al (2020), who found DON to the Skagerrak from Norwegian rivers to increase from 1990 to 2017, we detected no change in DON concentration. This may be due to the fact that our time series for DON starting in 2010 was much shorter than their dataset covering 27 years.…”
Section: Long Term Trendscontrasting
confidence: 83%
“…Higher temperature can induce species shifts and promote heterotrophic metabolism and thus affect organic matter recycling more strongly than the autotrophic process of carbon fixation (O'Connor et al, 2009). Air temperature at the closest weather station (since 1947) reflected globally increasing air temperature at a rate of 0.029 • C yr −1 at the southern Baltic Sea coast, similar to the trend reported by Deininger et al (2020) for all of Norway. The change point detected in the air temperature time series in 1988 was close to the global change point in 1987 attributed to rapid climate change and natural forcing (Reid et al, 2016).…”
Section: Long Term Trendssupporting
confidence: 64%
See 1 more Smart Citation
“…Our overarching hypothesis is that changes in concentrations of DON will track those of DOC and consequently the stoichiometry of DOM will remain consistent through time (Brookshire et al, 2007 ; Wymore et al, 2021c ). We also hypothesize that sites historically affected by acid deposition will be associated with increases in concentrations of DOC and DON assuming the same external forces are acting on each of these components of the DOM pool (Deininger et al, 2020 ). A global assessment of how riverine DOM is responding to global change is essential for robust regional and global scale predictive ecosystem models and for future watershed management protocols.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, several studies in the boreal region suggest that surface waters are becoming more nutrient‐poor over time. Here, observed long‐term declines in inorganic N in streams and rivers have been attributed to land cover change (Sarkkola et al 2012), declining N deposition (Deininger et al 2020), and interactions between land management and climate warming (Lucas et al 2016). More recently, attention has also been drawn to declines in inorganic P in Canadian (Eimers et al 2009) and Nordic rivers and lakes (Huser et al 2018; de Wit et al 2020), which may similarly arise from changes in climate, recovery from acid deposition, land‐use transitions and from emergent geochemical sinks (e.g., increase in Aluminum sinks) (Huser and Rydin 2005).…”
mentioning
confidence: 94%